Gender Differences in the Structure of Holland's Personality Model in South Korea. (August 2022) - Lee, Donghyuck; Lee, Hang-Shim; Na, Wooyoul; Hwang, Mae Hyang
This study examined the structure of Holland's personality model (HPM) among male and female South Korean college students using the Korean version of the Self-Directed Search (K-SDS) and investigated gender differences in the circular structure of HPM and circular plots of the K-SDS subscales (i.e., activities, competences, vocations, and self-estimates). The study outcomes were as follows: Our findings supported the validity of HPM among Korean college freshmen. However, there were gender differences in the fit between the data and the circular ordering model. Also, the differences in the realistic, investigative, artistic, social, enterprising, and conventional (RIASEC) circular plots and the magnitude of the correlations among the RIASEC types across the four subscales and gender were found. These results suggest that practitioners should cautiously interpret and communicate the results of the SDS to college students considering cultural and gender specificity. Implications and limitations of the present research are discussed.